Modelling of zinc (II) transport through a PC-88A supported liquid membrane - Tarditi, Ana Maria (2008)
Zinc has been permeated through a flat-sheet supported liquid membrane, using 2-ethylhexylphosphoric acid mono-2-ethylhexyl ester (PC-88A) in kerosene. Liquid-liquid experiments were conducted as a function of aqueous pH (1-6) to establish optimum conditions for both extraction and stripping of the metal. A mass-transfer model was developed to predict the extent of Zn(II) permeation through the supported liquid membrane (SLM) under different experimental conditions. The effect of stirring rate, carrier concentration and temperature upon metal transport has been evaluated. The metal flux has been derived taking into account stagnant layer aqueous diffusion and liquid membrane diffusion as controlling factors. The overall transport evaluated from the proposed resistances model was in reasonable agreement with those obtained from experimental data. Under the studied experimental conditions the resistance of the intrinsic organic phase is masked by the aqueous stagnant layer resistance; therefore the Zn (II) transport through the liquid membrane is mainly controlled by the hydrodynamic of the system.